EEG-Based Brain–Computer Interfaces for Communication and Rehabilitation of People with Motor Impairment: A Novel Approach of the 21st Century - Lazarou, Ioulietta; Nikolopoulos, Spiros; Petrantonakis, Panagiotis C.; Kompatsiaris, Ioannis; Tsolaki, Magda (Frontiers in Human Neuroscience, 2018)
People with severe motor impairment face many challenges in communication and control of the environment, whilst survivors from neurological disorders have increased demand for advanced, adaptive and personalized rehabilitation. The last decades many studies have underlined the importance of brain-computer interfaces (BCIs) with great contributions ranging from communication restoration to motor rehabilitation. In this work we review BCI research that focuses on noninvasive, electroencephalography (EEG)-based BCI systems for people with motor impairment as far as communication and rehabilitation aspects are concerned. More specifically we overview milestone approaches that are primarily intended to help severely paralyzed and/or locked-in state patients by using three different BCI modalities, i.e., slow cortical potentials, sensorimotor rhythms and P300 potentials as operational mechanisms. In addition, we review BCI systems with special emphasis on restoration of motor function for patients with spinal cord injury and chronic stroke. Finally, we summarize how EEG-based BCI systems have contributed to communication and rehabilitation of motor impaired people, stress out advantages and limitations and discuss the challenges that these systems should address in the future.